Cd-Free Cu2ZnSnS4 solar cell with an efficiency greater than 10% enabled by Al2O3 passivation layers. Issue 9 (30th July 2019) - Cui, Xin; Sun, Kaiwen; Huang, Jialiang; Yun, Jae S.; Lee, Chang-Yeh; Yan, Chang; Sun, Heng; Zhang, Yuanfang; Xue, Chaowei; Eder, Katja; Yang, Limei; Cairney, Julie M.; et al.
Abstract : Cd-Free CZTS solar cell with above 10% efficiency was achieved by an Al2 O3 passivation layer prepared by ALD. Abstract : Environmentally friendly earth-abundant Cd-free Cu2 ZnSnS4 (CZTS) solar cells have recently achieved increasing power conversion efficiency by using ZnSnO as the buffer layer. However, the large open circuit voltage ( V oc ) deficit remains the key concern. Here, we report a Cd-free CZTS solar cell that exhibits an energy conversion efficiency of 10.2% resulting from the application of an aluminium oxide (Al2 O3 ) passivation layer prepared by atomic layer deposition (ALD). We found that the application of full ALD cycles as well as trimethylaluminum (TMA) exposures resulted in a significant increase in V oc and relate this to the properties of the CZTS interface. Both processes facilitate the formation of a thicker Cu-deficient nanolayer with a higher concentration of Na and O, forming a homogeneous passivation layer across the CZTS surface. This nanolayer reduces the local potential fluctuation of band edges and leads to the widened electrical band gap and suppressed defects recombination at the heterojunction interface, thus improvement in V oc and device performance. The ability of nanolayers to alter the atomic composition in the near surface region of compound semiconductors might be beneficial for a wider range of semiconductor devices.